School-Based Interventions on Human Papillomavirus in Africa: A Systematic Scoping Review - Amzat, Jimoh; Kanmodi, Kehinde Kazeem; Aminu, Kafayat; Egbedina, Eyinade Adeduntan (Venereology (Basel, Switzerland), 2023)
School-age youth constitute a neglected but highly vulnerable group concerning sexual health risks in low-resource countries. Robust evidence concerning the research landscape of school-based interventions on human papillomavirus in Africa is currently lacking. Therefore, this systematic scoping review (SSR) aims to map evidence about school-based HPV interventions and identify emerging themes, gaps and lessons learned in Africa. This review was guided by Joanna Brigg’s Institute’s guidelines for SSRs and reported based on the Preferred Reporting Items for Systematic Reviews and Metanalysis for Scoping Reviews. Five databases—PubMed, CINAHL, PsycINFO, SCOPUS, and Allied and Complementary Medicine—were searched for relevant literature using appropriate search terms and Boolean operators. The retrieved literature was extracted, deduplicated and screened using the Rayyan software. Only those articles which met the eligibility criteria were included for data charting, collation, and summarization. Ten articles were included in this review. The articles demonstrate that a life-course approach is significant in health intervention. School-based health interventions help reach adolescents in a dynamic life stage, affecting their vulnerability to sexual health risks. The school-based interventions serve as an ideal platform to offer HPV peer education, improving their HPV knowledge and subsequent testing services and enhancing their acceptability for screening and vaccination. Cervical cancer education and screening can be effectively combined in HPV health services for women. While the studies are geographically diverse, such effective interventions, which help reduce bottlenecks in accessing HPV screening and vaccination, are very few in Africa. In conclusion, school-based intervention is a viable strategy that can be adopted for adolescent protection from HPV-induced diseases. However, the current evidence on the impact of these interventions, particularly HPV vaccination, is inadequate.